2016
DOI: 10.4103/0366-6999.185855
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correlation of Airway Pressure and Transpulmonary Pressure Stress Index on Respiratory Mechanics in Acute Respiratory Failure

Abstract: Background:Stress index at post-recruitment maneuvers could be a method of positive end-expiratory pressure (PEEP) titration in acute respiratory distress syndrome (ARDS) patients. However, airway pressure (Paw) stress index may not reflect lung mechanics in the patients with high chest wall elastance. This study was to evaluate the Paw stress index on lung mechanics and the correlation between Paw stress index and transpulmonary pressure (PL) stress index in acute respiratory failure (ARF) patients.Methods:Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The results showed that the loss of lung compliance consequent to lung overdistension was significantly greater in patients who used higher PEEP/FiO 2 tables to set PEEP than in those who used EIT. In addition, many other methods can guide PEEP titration, such as the lung P-V curve, esophageal pressure method [ 89 ], stress index method [ 90 ], and PEEP decreasing method [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the loss of lung compliance consequent to lung overdistension was significantly greater in patients who used higher PEEP/FiO 2 tables to set PEEP than in those who used EIT. In addition, many other methods can guide PEEP titration, such as the lung P-V curve, esophageal pressure method [ 89 ], stress index method [ 90 ], and PEEP decreasing method [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed angiotensin-converting enzyme 2 (ACE2) has an CoV-2) enters human cells. High values of strain are known to be harmful to the lung and to increase mortality [34][35][36][37][38][39][40][41][42] .…”
Section: Clinical Features and Possible Treatmentsmentioning
confidence: 99%
“…Apart from the physical alveolar disruption induced by MV, researchers realized that it was excessive lung volume which leads to overdistention of the lung, i.e., volutrauma, characterized by hyperpermeability of the alveolar-capillary barrier. [ 5 ] A classical experiment found that pulmonary edema and cellular ultrastructural abnormalities were encountered only in rats subjected to high V T but not in those in which lung distention was limited by thoracoabdominal strapping, which highlighted the effect of transpulmonary pressure instead of airway pressure during VILI. The importance of transpulmonary pressure and how it can predict the risk of VILI has been discussed elsewhere.…”
Section: Olecular M Echanisms Of mentioning
confidence: 99%